2015
DOI: 10.1039/c5an00617a
|View full text |Cite
|
Sign up to set email alerts
|

An instantly usable paper-based screen-printed solid-state KCl/Ag/AgCl reference electrode with long-term stability

Abstract: An instantly usable screen-printed paper-based Ag/AgCl electrode was fabricated for use as a cost-effective disposable reference electrode. The reference electrode showed potential stability for approximately 75 h. The setup time, which is less than 1 min, is much shorter than those for similar previously reported electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 25 publications
(50 reference statements)
0
30
0
Order By: Relevance
“…Similar works that have demonstrated uid transpiration driven by capillary forces due to the use of porous paper based substrates have been discussed in Section 3. 182 The methods of exible RE fabrication discussed within this section ( Fig. 3f) are also useful for the efficient design of such paperbased sensors.…”
Section: Flexible Reference Electrodesmentioning
confidence: 99%
“…Similar works that have demonstrated uid transpiration driven by capillary forces due to the use of porous paper based substrates have been discussed in Section 3. 182 The methods of exible RE fabrication discussed within this section ( Fig. 3f) are also useful for the efficient design of such paperbased sensors.…”
Section: Flexible Reference Electrodesmentioning
confidence: 99%
“…Shitanda et al in 2015 [74], reported a paper-based, screen-printed Ag/AgCl RE that featured a hydration time of less than a minute and a lifetime of up 75 hours. The RE was fabricated using a Ag/AgCl ink that was printed on one side of a water-repellent-treated paper substrate ( figure 7).…”
Section: Figurementioning
confidence: 99%
“…Hydration time of less than a minute, lifetime of up to 75 hours Impressively fast hydration time suitable for instant use such as laboratorian applications or instant sample analysis, very low cost Very short lifetime, unsuitable for any application requiring long term use [74] Substrate-Layer 1 Silver conductor-Layer 2 Silver/silver chloride-Layer 3 Photo-curable acrylic film containing immobilized sodium tetrakis [3,5bis(trifluoromethyl)phenyl] borate (NaTFPB) and trimethylocthylammonium chloride (TOMA-Cl)-Layer 4…”
Section: Metallized Hole Pvc Membranementioning
confidence: 99%
“…[13] Among these, the Ag|AgCl-based REs are common and more attractive because of easy fabrication, stable electrode potential, and their nontoxicity. For this reason, Ag|AgCl-based thin [17,18] and thick film [19][20][21][22] REs have also been explored recently. [8,10,16] However, as discussed earlier, due to rigidity of glass, it is difficult to use GREs in emerging application such as wearables' systems.…”
mentioning
confidence: 99%
“…[8,10,16] However, as discussed earlier, due to rigidity of glass, it is difficult to use GREs in emerging application such as wearables' systems. For this reason, Ag|AgCl-based thin [17,18] and thick film [19][20][21][22] REs have also been explored recently. Although both these types of REs have been shown to have good potential for wearable and disposable devices, they still have several limitations.…”
mentioning
confidence: 99%